Water electrolysis cell and method of manufacturing the same

CN116536676BActive Publication Date: 2026-10-30TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211472322.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-02-02
Filing Date
2022-11-23
Publication Date
2026-10-30
Estimated Expiration
2042-11-23

AI Technical Summary

Benefits of technology

[0013]在根据本公开的水电解槽中,催化剂层在水流动的方向上具有催化剂的高密度部分和低密度部分。在高密度部分产生的气泡比周围聚集更多并迅速增大,这促进了从催化剂表面的脱附,脱附的气泡与在低密度部分催化剂表面上的气泡合并,从而促进催化剂活性位点的恢复。结果,反应过程中的表观活性位点数目增加,水电解性能提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116536676B_ABST
    Figure CN116536676B_ABST
Patent Text Reader

Abstract

A water electrolyzer includes a proton-conducting electrolyte membrane, an anode catalyst layer laminated on one face of the electrolyte membrane, and a cathode catalyst layer laminated on the other face of the electrolyte membrane. At least one of the anode catalyst layer and the cathode catalyst layer includes, in the in-plane direction of the anode catalyst layer and the cathode catalyst layer, a portion with a high catalyst density and a portion with a lower catalyst density than the portion with the high catalyst density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a water electrolysis cell for water electrolysis and a method for manufacturing the same. Background Technology

[0002] Japanese Unexamined Patent Application (JP2004-360076A) with publication number 2004-360076 discloses a method for manufacturing an electrode. In this method, an electrode is obtained in which the distribution of a solid polymer electrolyte or the like in an electrode catalyst layer is adjusted. Specifically, the method includes: a step of coating an ink containing a mixture of catalyst and electrolyte components onto a sheet member and drying it; a step of repeating this step twice to form two layers; and a step of transferring the two layers onto an electrolyte membrane.

[0003] Japanese Unexamined Patent Application (JP2015-506414A) with Publication No. 2015-506414 discloses a method for manufacturing a catalyst electrode. In this method, the electrode is manufactured by depositing and curing catalyst ink on a carrier film, and then bonding it to an electrolyte membrane.

[0004] Japanese Unexamined Patent Application (JP2000-26986A) with Publication No. 2000-26986 discloses water electrolysis using a solid electrolyte type water electrolysis device. The solid electrolyte type water electrolysis device has an electrolytic cell 1. Platinum group metals are plated on both sides of a solid electrolyte membrane 2 in the electrolytic cell 1. Porous electrodes 3 are disposed on the plating on both sides of the solid electrolyte membrane 2. Electrode plates 4 are disposed on the outer side of each porous electrode 3. In this solid electrolyte type water electrolysis device, iridium (Ir) or ruthenium (Ru) is used as the platinum group metal, and water electrolysis is carried out at 60°C to 120°C. Summary of the Invention

[0005] In water electrolysis, it is crucial to rapidly remove the generated gases from the electrolyzer. In related technologies, oxygen bubbles generated during water electrolysis adhere to and remain on the surface of the catalyst's active sites until they grow to a certain size. As long as oxygen bubbles remain on the surface of the catalyst's active sites, the water electrolysis performance deteriorates. Therefore, in related technologies, the number of apparent catalyst active sites available for water electrolysis decreases, leading to a deterioration in water electrolysis performance.

[0006] This disclosure promotes the emission of generated gases to improve water electrolysis efficiency.

[0007] A water electrolyzer according to one aspect of this disclosure includes: a proton-conducting electrolyte membrane; an anode catalyst layer laminated on one side of the electrolyte membrane; and a cathode catalyst layer laminated on the other side of the electrolyte membrane. At least one of the anode catalyst layer and the cathode catalyst layer includes, in the in-plane direction of the anode catalyst layer and the cathode catalyst layer, a portion with a high catalyst density and a portion with a lower catalyst density compared to the portion with the high catalyst density.

[0008] In the aforementioned water electrolyzer, the anode catalyst layer may include a portion with high catalyst density in the in-plane direction of the anode catalyst layer, and a portion with lower catalyst density compared to the portion with high catalyst density.

[0009] In the aforementioned water electrolyzer, the catalyst density of the portion with high catalyst density can be more than 1.1 times higher than that of the portion with low catalyst density.

[0010] In the aforementioned water electrolyzer, the catalyst in the anode catalyst layer may contain iridium oxide.

[0011] In the aforementioned water electrolyzer, the catalyst in the cathode catalyst layer may contain platinum / carbon and ionomers.

[0012] A method for manufacturing a water electrolyzer according to one aspect of this disclosure includes: placing a back plate on a fixed platform having a plurality of holes; forming recesses into the holes on the surface of the back plate by suctioning the back plate from the holes; applying catalyst ink to the surface of the back plate to obtain a catalyst ink layer including protrusions formed at the locations of the recesses; sandwiching the layer between smooth plates and heating and pressurizing it to obtain an anode catalyst layer, wherein the compressed portions of the protrusions in the anode catalyst layer become portions exhibiting a higher catalyst density than other portions.

[0013] In the water electrolyzer according to this disclosure, the catalyst layer has a high-density portion and a low-density portion in the direction of water flow. Bubbles generated in the high-density portion aggregate more extensively and rapidly increase in size than those surrounding the catalyst, promoting desorption from the catalyst surface. The desorbed bubbles merge with bubbles on the catalyst surface in the low-density portion, thereby promoting the recovery of active sites on the catalyst. As a result, the number of apparent active sites increases during the reaction process, and the water electrolysis performance is improved. Attached Figure Description

[0014] The features, advantages, and technical and industrial significance of exemplary embodiments of the present invention will now be described with reference to the accompanying drawings, wherein like symbols denote like elements, and wherein:

[0015] Figure 1 This is a plan view of water electrolysis cell 10;

[0016] Figure 2 This is a conceptual diagram showing the layered structure of the water electrolysis unit 10a in the water electrolysis cell 10;

[0017] Figure 3 This is a plan view showing the anode catalyst layer 12;

[0018] Figure 4 This is a cross-sectional view showing the anode catalyst layer 12;

[0019] Figure 5 This is a diagram showing the fabrication process of the anode catalyst layer 12;

[0020] Figure 6 This is a diagram showing the fabrication process of the anode catalyst layer 12;

[0021] Figure 7 This is a diagram showing the fabrication process of the anode catalyst layer 12;

[0022] Figure 8A These are diagrams illustrating the results of the embodiments; and

[0023] Figure 8B This is a graph showing the results of the comparative examples. Detailed Implementation

[0024] 1. Structure of a water electrolysis cell

[0025] Figure 1 and Figure 2 This is a diagram illustrating a water electrolyzer 10 according to an embodiment. The water electrolyzer 10 is a unit element for decomposing pure water into hydrogen and oxygen. Multiple such water electrolyzers 10 are stacked together to form a water electrolyzer stack. Figure 1 This is a plan view of water electrolysis cell 10. Figure 2 It is along Figure 1 A partial sectional view of line II-II in the middle. Figure 2 This is a diagram showing the layered structure of a water electrolysis unit 10a, which is the part of the water electrolysis cell 10 in which water electrolysis is performed.

[0026] The water electrolyzer 10 consists of multiple layers, one of which serves as an oxygen-generating electrode (anode) and another as a hydrogen-generating electrode (cathode), with a solid polymer electrolyte membrane 11 inserted between them. The anode comprises an anode catalyst layer 12, an anode gas diffusion layer 13, and an anode diaphragm 14, sequentially laminated from the solid polymer electrolyte membrane 11 side. Conversely, the cathode comprises a cathode catalyst layer 15, a cathode gas diffusion layer 16, and a cathode diaphragm 17, sequentially laminated from the solid polymer electrolyte membrane 11 side. Here, the water electrolyzer electrode assembly is a laminate of the solid polymer electrolyte membrane 11, the anode catalyst layer 12 disposed on the anode side of the solid polymer electrolyte membrane 11, and the cathode catalyst layer 15 disposed on the cathode side of the solid polymer electrolyte membrane 11. The typical thickness of the water electrolyzer electrode assembly is approximately 0.4 mm. The typical thickness of the water electrolyzer 10 at the water electrolyzer unit 10a is approximately 1.3 mm. For example, each layer is as follows.

[0027] 1.1 Solid polymer electrolyte membrane

[0028] The solid polymer electrolyte membrane 11 is a type of membrane with proton conductivity. The material (electrolyte) constituting the solid polymer electrolyte membrane 11 of this embodiment is a solid polymer material, examples of which include proton-conducting ion exchange membranes made of fluororesins, hydrocarbon resins, etc. This exhibits good proton conductivity (electrical conductivity) under humid conditions. A more specific example is a membrane made of Nafion (registered trademark), which is a perfluorinated electrolyte. The thickness of the solid polymer electrolyte membrane 11 is not particularly limited and can be 100 μm or less, preferably 50 μm or less, and more preferably 30 μm or less.

[0029] 1.2. Anode catalyst layer

[0030] The anode catalyst layer (oxygen electrode catalyst layer) 12 is a layer containing a catalyst, said catalyst being at least one of noble metal catalysts such as platinum (Pt), ruthenium (Ru), iridium (Ir), and their oxides. More specifically, examples of catalysts include platinum, iridium oxide, ruthenium oxide, iridium-ruthenium oxide, and mixtures thereof. Examples of iridium oxides include iridium oxide (IrO2, IrO3), iridium-tin oxide, iridium-zirconium oxide, etc. Examples of ruthenium oxides include ruthenium oxide (RuO2, Ru2O3), ruthenium-tantalum oxide, ruthenium-zirconium oxide, ruthenium-titanium oxide, ruthenium-titanium-cerium oxide, etc. Examples of iridium-ruthenium oxides include iridium-ruthenium-cobalt oxide, iridium-ruthenium-tin oxide, iridium-ruthenium-iron oxide, iridium-ruthenium-nickel oxide, etc.

[0031] The anode catalyst layer 12 here may contain ionomers. By containing ionomers, coatability can be improved, and the hydrophilicity of the ionomers can promote the permeation of water supplied during water splitting. Examples of ionomers contained in the anode catalyst layer 12 include ionomers containing perfluorinated electrolytes, which are electrolytes used in solid polymer electrolyte membranes.

[0032] Furthermore, in this embodiment, the anode catalyst layer 12 has a distribution of high and low catalyst densities in its layer plane direction. Figure 3 and Figure 4 It is a diagram used to illustrate it. Figure 3 This is a plan view of the anode catalyst layer 12, showing the layers of the anode catalyst layer 12. Figure 4 It is along Figure 3 A cross-sectional view along line IV-IV shows the cross-section of the anode catalyst layer 12 in the thickness direction.

[0033] The anode catalyst layer 12 according to this embodiment contains the catalyst as described above, and has portions with high catalyst density (high-density portions) distributed in the layer planar direction. For example, in Figure 3 and 4 In the example shown, the high-density portion 12a (indicated by the symbol 12a) is distributed along the plane of the anode catalyst layer 12. The high-density portion 12a is... Figure 3 The part enclosed by the dotted line. Figure 3 In this designation, only a portion of the high-density portion is indicated by the symbol 12a to reduce repetition. The portion indicated by the symbol 12b is the portion with a catalyst density lower than that of the high-density portion 12a (low-density portion 12b). Furthermore, it is preferable to provide the high-density portion 12a along the entire thickness direction of the anode catalyst layer 12.

[0034] The difference between the density of the catalyst in the high-density portion 12a and the density of the catalyst in the low-density portion 12b is sufficient, as long as the density of the catalyst in the high-density portion 12a is higher than the density of the catalyst in the low-density portion 12b. It is sufficient if the density of the catalyst in the high-density portion 12a is greater than 1.0 times the density of the catalyst in the low-density portion 12b. From the viewpoint of obtaining higher efficiency, the density of the catalyst in the high-density portion 12a is preferably 1.1 times or more, more preferably 1.2 times or more, than specifically limited to the density of the catalyst in the low-density portion 12b. On the other hand, although there is no particular upper limit, from the viewpoint of ensuring the flowability of water and gas, the upper limit is preferably no more than 2 times.

[0035] The distribution of the high-density portion 12a in the layer plane direction is not particularly restricted, but from Figure 3From this perspective, the ratio of the area of ​​the high-density portion 12a to the area of ​​the anode catalyst layer 12 is preferably 5% or more and 80% or less. When it is below this range, the effect of the high-density portion 12a may be relatively small. On the other hand, when it is above this range, the flow of water and generated oxygen may be hindered. This ratio is more preferably 10% or more and 60% or less, and even more preferably 15% or more and 40% or less.

[0036] Although there are no particular restrictions, the high-density portions 12a are preferably arranged across the entire anode catalyst layer 12. In this arrangement, the high-density portions 12a adjacent to each other in the flow direction are preferably staggered in the width direction (a direction orthogonal to the flow direction), i.e., staggered arrangement, such as... Figure 3 As shown.

[0037] The shape of each high-density portion 12a is not particularly limited, and can be circular in the plan view as in this embodiment. The shape of each high-density portion 12a can be triangular, quadrilateral, or some other polygon, ellipse, sector, or irregular shape. Furthermore, the size of each high-density portion 12a is not particularly limited. For example, when each high-density portion 12a is circular in the plan view, its diameter can be approximately 5 mm to 30 mm. For example, when each high-density portion 12a is not circular in the plan view, its area in the plan view can be approximately 19 mm². 2 Up to 710mm 2 .

[0038] 1.3. Cathode catalyst layer

[0039] Known catalysts can be used as catalysts contained in the cathode catalyst layer 15, examples of which include platinum, platinum-coated titanium, platinum / carbon, palladium / carbon, cobalt oxime, nickel oxime, etc. The cathode catalyst layer 15 here may contain ionomers. Containing ionomers can improve coatability. Examples of ionomers contained in the cathode catalyst layer 15 include ionomers made from perfluorinated electrolytes, which are electrolytes used for solid polymer electrolyte membranes.

[0040] Note that the cathode catalyst layer 15 may also have portions corresponding to the high-density portion 12a and the low-density portion 12b described with respect to the anode catalyst layer 12. Accordingly, the same effects as described below can be obtained in the generation and emission of hydrogen.

[0041] 1.4. Anode Gas Diffusion Layer

[0042] Known components can be used for the anolyte gas diffusion layer 13, which is composed of components that are breathable and conductive. Specific examples include porous conductive components made of sintered bodies of metal fibers (e.g., titanium fibers) or metal particles (titanium particles).

[0043] 1.5. Cathode Gas Diffusion Layer

[0044] Known components can be used for the cathode gas diffusion layer 16, which is composed of components that are breathable and conductive. Specific examples include porous components, such as carbon cloth, carbon paper, etc.

[0045] 1.6. Anode diaphragm

[0046] A known component can be used for the anode diaphragm 14, which is a component provided with a channel (groove) 14a through which pure water is supplied to the anode gas diffusion layer 13, and the generated oxygen flows through the channel. Figure 1 It can be seen that the anode diaphragm 14 has a position on the outside of the water electrolysis unit 10a and a channel 14a ( Figure 2 The H2O inlet is located at the first end side of the part. 进1 and inlet H2O 进2 And a water and oxygen outlet (O2 / H2O) is provided at a portion of the second end side of channel 14a. 出 Water and hydrogen outlet H2 / H2O 出 Now, channel 14a connects to the inlet H2O at its first end. 进1 Connected at its second end to the water and oxygen outlets O2 / H2O 出 Connected.

[0047] 1.7. Cathode diaphragm

[0048] A known component can be used for the cathode diaphragm 17, which is a component provided with a channel (groove) 17a through which separated hydrogen and accompanying water flow. Figure 1 It can be seen that the cathode diaphragm 17 has a position on the outside of the water electrolysis unit 10a and a channel 17a ( Figure 2 The H2O inlet is located at the first end side of the part. 进1 and inlet H2O 进2 And a water and oxygen outlet (O2 / H2O) is provided at a portion of the second end side of channel 17a. 出 Water and hydrogen gas outlet H2 / H2O 出 Now, channel 17a connects to the inlet H2O at its first end. 进2 Connected at its second end to water and hydrogen outlet H2 / H2O 出 Connected.

[0049] 1.8. Hydrogen is produced by the water electrolysis cell, with effects such as...

[0050] The aforementioned water electrolyzer 10 produces hydrogen and oxygen from pure water as follows. Therefore, in addition to the above, the water electrolyzer and water electrolysis stack according to this disclosure can be equipped with known components and structures necessary for hydrogen production. Pure water (H2O) is supplied from channel 14a of the anode diaphragm 14 to the anode (oxygen generating electrode). An electric current is applied across the anode and cathode, and at the anode catalyst layer 12 where the applied potential is applied, the pure water is decomposed into oxygen, electrons, and protons (H2O). + At this point, protons pass through the solid polymer electrolyte membrane 11 to reach the cathode catalyst layer 15. Meanwhile, electrons separated at the anode catalyst layer 12 reach the cathode catalyst layer 15 via an external circuit. The protons then accept electrons at the cathode catalyst layer 15 to produce hydrogen (H2). The produced hydrogen gas reaches the cathode diaphragm 17 and exits through channel 17a. Note that oxygen separated at the anode catalyst layer 12 reaches the anode diaphragm 14 and exits through channel 14a.

[0051] Focusing on the anode catalyst layer 12 in the production of hydrogen and oxygen, water is supplied to the anode catalyst layer 12 from channel 14a of the anode diaphragm 14 via the anode gas diffusion layer 13. For example... Figure 1 As shown, the water generally flows from the inlet H2O 进1 O2 / H2O outlet towards water and oxygen 出 Therefore, water and the generated oxygen generally flow along the anode catalyst layer 12. Figure 3 The water flows in the direction of the straight arrow. Then, due to the catalyst in the anode catalyst layer 12, water decomposes and produces oxygen, thereby generating oxygen bubbles. Now, in this embodiment, a high-density section 12a with a high catalyst density is provided. More oxygen generated by water electrolysis accumulates in the high-density section 12a, and bubbles desorb from the catalyst surface (catalyst active sites) faster than in other sections. Therefore, oxygen bubbles that desorb faster than their surroundings diffuse with the water flow to the low-density section 12b, and it is believed that these bubbles contact the oxygen bubbles remaining on the catalyst surface in the low-density section 12b, removing oxygen from the catalyst surface. As a result, oxygen bubble desorption from the catalyst can be promoted not only in the high-density section 12a but also in the low-density section 12b. Therefore, oxygen (water decomposition) can be generated at a high frequency at the catalyst. As a result, high electrolysis performance can be maintained during long-term water electrolysis operation.

[0052] In the prior art, the concentration of the catalyst is uniform in the direction of water flow, which may result in insufficient promotion of the desorption of generated oxygen from the catalyst. Furthermore, when there is a difference in catalyst density along the thickness direction of the anode catalyst layer, or when the catalyst as a whole is made with a high density, the gaps between the high-density portions are small, which may hinder the diffusion and flow of water as a component. That is, the catalyst density of the anode catalyst layer 12 according to this embodiment varies in the direction of water flow. Therefore, the aforementioned effect of oxygen generated in the high-density portions of the catalyst can promote the desorption of bubbles from the catalyst throughout the entire anode catalyst layer, while simultaneously promoting the diffusion of water in the low-density portions of the catalyst.

[0053] 2. Manufacturing method

[0054] For example, the water electrolysis cell 10 described above can be manufactured as follows.

[0055] 2.1. Preparation of the anode catalyst layer

[0056] As described above, the high-density portion 12a and the low-density portion 12b of the catalyst coexist in the anode catalyst layer 12, and such a form can be prepared, for example, as follows.

[0057] First, catalyst ink 22 is obtained by mixing an anode catalyst, an ionomer, deionized water, and an alcohol.

[0058] like Figure 5 As shown, the backplate 21 (e.g., a Teflon (registered trademark) plate) is placed on the mounting table 20 to apply catalyst ink 22. Figure 6 The mounting platform 20 is provided with a plurality of holes 20a. The holes 20a are located at positions corresponding to the positions used to form the high-density portion 12a. For example... Figure 5 As shown by the straight arrow, a recess 21a is formed in the surface of the back plate 21 on which the catalyst ink 22 is to be coated by drawing back plate 21 through orifice 20a using a pump. Then, the catalyst ink 22 is coated onto the surface of the back plate 21 using a coater, forming a layer of catalyst ink 22. At this time, the surface of the catalyst ink 22 layer is made flat, as shown... Figure 6 As shown. Therefore, in the applied catalyst ink 22, a protrusion 22a is formed at the position of the recess 21a. The catalyst ink 22 is dried in this state and then sandwiched between smooth plates 23 (such as stainless steel plates), as shown. Figure 7As shown, the protrusions 22a formed on the dried catalyst ink 22 are smoothed by hot pressing (heating and pressurizing) as indicated by the straight arrow. Therefore, the protrusions 22a are greatly compressed, and the catalyst density therein increases, thus forming a high-density portion 12a. This forms an anode catalyst layer 12 with portions of high catalyst density and portions of low catalyst density in the in-plane direction (the direction of water flow), as shown. Figure 3 and 4 As shown.

[0059] 2.2. Preparation of the cathode catalyst layer

[0060] For example, cathode catalyst layer 15 is prepared as follows: Weigh the cathode catalyst, ionomer, deionized water, and alcohol, and mix them in a beaker. Coat the solution onto a backing plate (e.g., a Teflon plate) and dry it. This yields cathode catalyst layer 15.

[0061] 2.3. Preparation of water electrolysis membrane electrode assembly

[0062] After the anode catalyst layer 12 and cathode catalyst layer 15 prepared above are disposed on the front and back sides of the solid polymer electrolyte membrane 11, the back plate is removed and hot pressing is performed. Thus, the solid polymer electrolyte membrane 11, the anode catalyst layer 12, and the cathode catalyst layer 15 are bonded together, thereby obtaining a water electrolysis membrane electrode assembly.

[0063] 2.4. Manufacturing of water electrolysis cells

[0064] according to Figure 1 The layered layout shown involves pressing an anode gas diffusion layer 13, a cathode gas diffusion layer 16, an anode diaphragm 14, and a cathode diaphragm 17 onto the front and back of the obtained water electrolysis membrane electrode assembly, thereby obtaining a water electrolysis cell.

[0065] 2.5. Effects, etc.

[0066] According to the manufacturing method of the water electrolyzer described above, the high-density portion 12a in the anode catalyst layer 12 can be formed particularly easily and efficiently, thereby producing a highly productive water electrolyzer. In addition to preparing the anode catalyst layer 12 using catalyst ink 22 as described above, the anode catalyst layer can be similarly prepared by a printing method of mixing dry powder and compacting it under heat, or by a coating method such as inkjet printing.

[0067] 3. Example

[0068] In the embodiments, a water electrolyzer is manufactured in which the aforementioned high-density portion is formed in the anode catalyst layer. The water electrolyzer according to the embodiments is compared with a related water electrolyzer manufactured as a comparative example that does not have a high-density portion.

[0069] 3.1. Manufacturing of the water electrolysis cell according to the embodiment

[0070] 3.1.1. Preparation of the anode catalyst layer

[0071] First, 48.0 g of anode catalyst (iridium oxide catalyst (manufactured by Umicore)), 9.6 g of proton-conducting ionomer (manufactured by AGC), 36.0 g of deionized water and alcohol (21.5 g of 1-propanol and 33.2 g of ethanol) were mixed in a beaker and dispersed using an ultrasonic homogenizer to obtain catalyst ink 22.

[0072] like Figure 5 As shown, the back plate 21 (Teflon (registered trademark) plate) is placed on the fixed platform 20 for coating the catalyst ink 22. Figure 6 A pump is used to draw water from the back plate 21 through a hole 20a provided on the fixed platform 20, thereby forming a recess 21a in the back plate 21 to be coated with catalyst ink 22. The hole 20a is circular and has a diameter of 20 mm. Figure 3 As shown, the holes 20a are arranged in a staggered pattern. The spacing a between adjacent holes 20a in the direction of water flow (see Figure 1) Figure 3 The distance between the centers of adjacent holes 20a in the direction of water flow is set to 15mm, and the pitch (p1) is (see...). Figure 3 The spacing p2 in the direction perpendicular to the water flow direction is set to 35mm. Figure 3 It is also set to 35mm.

[0073] Subsequently, a coater is used to apply catalyst ink 22 onto the back plate 21, thereby smoothing the surface, such as... Figure 6 As shown. Thus, in the coated catalyst ink 22, a protrusion 22a is formed at the position of the recess 21a. In this state, the catalyst ink 22 is dried at 85°C for 5 minutes, and then as shown... Figure 7 The sample is sandwiched between smooth plates 23 (stainless steel plates) and hot-pressed at 130°C for 4 minutes. As a result, the protrusions 22a formed on the dried catalyst ink 22 become smooth. In this way, an anode catalyst layer is obtained by mixing iridium oxide catalyst and ionomer in a weight ratio of 1:0.2. In this anode catalyst layer, the unit volume weight of the low-density portion is 1, and the unit volume weight of the high-density portion is 1.24.

[0074] 3.1.2. Preparation of the cathode catalyst layer

[0075] First, 6.1 g of cathode catalyst (Pt / carbon (18% Pt loading, manufactured by Cataler), 6.0 g of proton-conducting ionomer (manufactured by AGC), 88.4 g of deionized water, and 45.2 g of alcohol (ethanol) were weighed and placed in a beaker, and dispersed using an ultrasonic homogenizer. The solution was then coated onto a 1.0 mm thick backing plate (Teflon plate) and dried at 85 °C for 5 minutes. As a result, a cathode catalyst layer in which carbon and ionomer were mixed in a weight ratio of 1:1.2 was obtained.

[0076] 3.1.3. Preparation of water electrolysis membrane electrode assembly

[0077] The anode and cathode catalyst layers prepared above were arranged before and after a 15 μm thick solid polymer electrolyte membrane (manufactured by Gore, Japan). The backing plate was then removed, and the membrane was hot-pressed at 130°C and 130 kPa for at least 4 minutes to obtain the water electrolysis membrane electrode assembly. Now, pressing was performed at a temperature higher than the softening point of the ionomer to produce an anode catalyst layer with high density and uniform thickness. Note that the area of ​​the layer in the water electrolysis membrane electrode assembly (area in the plan view) is 300 cm². 2 .

[0078] 3.1.4. Manufacturing of water electrolysis cells

[0079] according to Figure 1 The layer layout shown involves pressing the anode gas diffusion layer (platinum-deposited titanium fiber), the cathode gas diffusion layer (carbon fiber), the anode diaphragm, and the cathode diaphragm onto the front and back of the obtained water electrolysis membrane electrode assembly, thereby obtaining a water electrolysis cell.

[0080] 3.2. Manufacturing of the water electrolyzer according to the comparative example

[0081] The water electrolyzer was prepared in the same manner as in the examples, except that a non-porous surface plate was used instead of the stationary platform used to prepare the anode catalyst layer according to the examples. This resulted in a water electrolyzer with a uniform density of iridium oxide catalyst in the in-plane direction of the anode catalyst layer.

[0082] 3.3. Evaluation Test

[0083] The following evaluation was conducted on the manufactured water electrolyzer. Sufficient pure water (<1 μS / cm) was circulated through the inlets of the anode and cathode diaphragms. The electrolyzer temperature was 60°C, and the applied voltage was adjusted to achieve an electrolysis current density of 2.5 A / cm². 2 Water electrolysis was carried out for 5 hours. Afterwards, the ratio of the electrolysis voltage V5 after 5 hours to the electrolysis voltage V0 at the beginning of the experiment (V5 / V0×100%) was calculated as the water electrolysis activity maintenance rate.

[0084] 3.4. Results

[0085] Figure 8A and 8B The cross-section of the anode catalyst layer of the manufactured water electrolyzer is shown. Figure 8A It is a cross-section of the high-density portion of the anode catalyst layer of the water electrolyzer according to the embodiment. Figure 8B This is based on a cross-section of the anode catalyst layer in a comparative example water electrolyzer. From... Figure 8A and Figure 8B It is understood that the high-density portion of the embodiment has the same thickness (7 μm) as the anode catalyst layer of the comparative example, but the high-density portion of the embodiment is denser than that of the anode catalyst layer of the comparative example. Note that in the water electrolyzer according to the embodiment, the portion of the anode catalyst layer other than the high-density portion (low-density portion) has the same cross-section as that of the anode catalyst layer according to the comparative example.

[0086] The water electrolysis activity retention rate of the water electrolyzer according to the embodiment is 100.6%, thus achieving a high retention rate. In contrast, the water electrolysis activity retention rate of the comparative example is 97.7%, which is lower than the water electrolysis activity retention rate of the water electrolyzer according to the embodiment.

Claims

1. A water electrolysis cell, characterized in that, include: Proton-conducting electrolyte membrane; An anode catalyst layer, which is laminated onto one side of the electrolyte membrane; and A cathode catalyst layer is laminated on the other side of the electrolyte membrane. At least one of the anode catalyst layer and the cathode catalyst layer includes, in the in-plane direction of the anode catalyst layer and the cathode catalyst layer, a portion with a high catalyst density and a portion with a lower catalyst density compared to the high-density portion, wherein the catalyst density of the high-density portion is more than 1.1 times higher than the catalyst density of the low-density portion. Wherein, the area of ​​the high-density portion of the catalyst is in a ratio of 5% to 80% of the area of ​​the anode catalyst layer, and The high-density portions of the catalyst are arranged on the entire anode catalyst layer, and adjacent high-density portions in the flow direction are staggered in the width direction.

2. The water electrolysis cell according to claim 1, characterized in that, The anode catalyst layer includes a portion with high catalyst density in the in-plane direction of the anode catalyst layer, and a portion with lower catalyst density compared to the high-density portion.

3. The water electrolysis cell according to claim 1 or 2, characterized in that, The catalyst in the cathode catalyst layer contains platinum / carbon and ionomers.

4. The water electrolysis cell according to claim 1 or 2, characterized in that, The catalyst in the anode catalyst layer contains iridium oxide.

5. The water electrolysis cell according to claim 4, characterized in that, The catalyst in the cathode catalyst layer contains platinum / carbon and ionomers.

6. A method for manufacturing a water electrolysis cell, characterized in that, include: Place the backplate on a mounting platform with multiple holes; By drawing the back plate through the hole, a recess is formed on the surface of the back plate that is recessed into the hole; The catalyst ink is applied to the surface of the back plate to obtain a catalyst ink layer, which includes a protrusion formed at the recessed location. as well as The catalyst ink layer is sandwiched between smooth plates and heat and pressure are applied to obtain an anode catalyst layer, in which the compressed portions of the protrusions become portions exhibiting a higher catalyst density than other portions. Wherein, the area of ​​the high-density catalyst portion is in a ratio of 5% to 80% of the area of ​​the anode catalyst layer, and The high-density catalyst sections are arranged on the entire anode catalyst layer, and the high-density catalyst sections that are adjacent to each other in the flow direction are staggered in the width direction.

Citation Information

Patent Citations

  • Solid electrolyte type water electrolysis apparatus and water electrolysis method using the apparatus

    JP2000026986A

  • Solid electrolyte membrane and manufacturing method therefor

    JP2004360076A

  • Porous electrodes for proton exchange membranes

    JP2015506414A

  • Group of cells for power adaptation of electrochemical reactors

    US20190221873A1